Preprocedural N‐Terminal Pro‐Brain Natriuretic Peptide (NT‐proBNP) Is Similar to the Mehran Contrast‐Induced Nephropathy (CIN) Score in Predicting CIN Following Elective Coronary Angiography. Issue 4 (17th April 2015) - Liu, Yong; He, Yi‐ting; Tan, Ning; Chen, Ji‐yan; Liu, Yuan‐hui; Yang, Da‐hao; Huang, Shui‐Jin; Ye, Piao; Li, Hua‐long; Ran, Peng; Duan, Chong‐yang; Chen, Shi‐qun; et al.
Abstract : Background: N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) has been associated with important risk factors for contrast‐induced nephropathy (CIN). However, few studies have investigated the predictive value of NT‐proBNP itself. This study investigated whether levels of preprocedural NT‐proBNP could predict CIN after elective coronary angiography as effectively as the Mehran CIN score. Methods and Results: We retrospectively observed 2248 patients who underwent elective coronary angiography. The predictive value of preprocedural NT‐proBNP for CIN was assessed by receiver operating characteristic and multivariable logistic regression analysis. The 50 patients (2.2%) who developed CIN had higher Mehran risk scores (9.5±5.1 versus 4.8±3.8), and higher preprocedural levels of NT‐proBNP (5320±7423 versus 1078±2548 pg/mL, P <0.001). Receiver operating characteristic analysis revealed that NT‐proBNP was not significantly different from the Mehran CIN score in predicting CIN (C=0.7657 versus C=0.7729, P =0.8431). An NT‐proBNP cutoff value of 682 pg/mL predicted CIN with 78% sensitivity and 70% specificity. Multivariable analysis suggested that, after adjustment for other risk factors, NT‐proBNP >682 pg/mL was significantly associated with CIN (odds ratio: 4.007, 95% CI: 1.950 to 8.234; P <0.001) and risk of death (hazard ratio: 2.53; 95% CI: 1.49 to 4.30; P =0.0006). Conclusions: Preprocedural NT‐proBNP >682 pg/mL was significantly associated with the risk of CIN and death. NT‐proBNP, like the Mehran CIN score, may be another useful and rapid screening tool for CIN and death risk assessment, identifying subjects who need therapeutic measures to prevent CIN.